Interaction of Ammonifying Bacteria and AMF Associated With Pioneer Plants in Ex-Gold Mining - Hamzah Hamzah; Jenny Rumondang; Ria Rif’atunidaudina; Rajjitha Handayani; Suci Ratna Puri; Rizki Ayu Hardiyanti; Dian Nisya (Universitas Pattimura, 2026)
Gold mining activities degrade soil physical and chemical properties, increasing compaction, reducing drainage and aeration, lowering productivity, and limiting plant growth. This study evaluated soil fertility, physical and chemical characteristics of ex-illegal gold mining land, and identified arbuscular mycorrhizal fungi (AMF) species and ammonifying bacteria associated with pioneer plants used for phytoremediation. The results showed that high clay content limited water and nutrient infiltration. The average clay content increased from 42.41% in 2019 to 45.12% in 2021. Soil pH (H₂O and KCl) was acidic, ranging from 4.20 to 5.92. Organic carbon (0.96–1.87%) and total nitrogen (0.11–0.26%) were classified as low, indicating poor soil fertility. Among pioneer plants, Melastoma malabathricum showed the highest AMF spore abundance, with 37, 30, and 29 spores per 50 g of soil in 2019, 2020, and 2021, respectively. The highest population of ammonifying bacteria was found in the 2021, with a count of 46.3 x 105 individuals per gram of soil. This study aims to identify the interactions between AMF and ammonifying bacteria associated with pioneer plants to support phytoremediation activities on ex-illegal gold mining land.